Investigation on Electrochemical Property of AB/AI2O3- coated Li-excess Mn-based Layered Oxides. (May 2016) - Kobayashi, H; Takada, K; Arachi, Y; Okumura, T; Shikano, M; Nitani, H
Abstract: The AB and/or Al2 O3 -coated Li1.20 Mn0.55 Ni0.16 Co0.09 O2 were prepared by the mechanochemical reaction. The optimal condition for sample preparation was selected to be the rotation speed of 2000 rpm and the reaction time of 5 minutes by SEM and XANES measurements. Surface analysis using SEM and XANES data demonstrated that all the samples were rather uniformly covered with AB and/or nano-AEO3 particles. The AEO3 - coated samples showed less discharge capacity and C-rate performance compared with the pristine sample, while the AB/Al2 O3 -coated sample showed almost the same discharge capacity and C-rate performance and had better cycle performance at 318 K compared with the pristine sample. These results demonstrate that the mechanochemical AB/Al2 O3 -coating process is an effective way of improving the cycle performance at high temperature without degrading the discharge capacity and C-rate performance.